Evidence of occupational accidents with equipment in mining a systematic review protocol - Joana Duarte (2018)
Mining industry due to its great technical challenges continues to be one of the main high-risk industries. Many features can be attributed to this issue, such as workers age and experience, but also to environmental factors as well as equipment failure and misuse. This systematic review protocol outlines the principal procedures to conduct a systematic review which intends to find evidence of occupational accidents due to mining equipment usage. In order to accomplish this primary objective, the main engineering databases and journals were selected (i.e. Scopus, Science Direct and Web of Science) and a set of keywords was defined to latter sequenced combination. The selection process of the papers is also described, in an attempt to contribute to further research on this field. All of the data treatment is detailed, including the risk of bias and attempts to manage it.